2013
DOI: 10.1371/journal.pone.0055644
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of 12 Strains of Erwinia amylovora Identifies a Pan-Genome with a Large Conserved Core

Abstract: The plant pathogen Erwinia amylovora can be divided into two host-specific groupings; strains infecting a broad range of hosts within the Rosaceae subfamily Spiraeoideae (e.g., Malus, Pyrus, Crataegus, Sorbus) and strains infecting Rubus (raspberries and blackberries). Comparative genomic analysis of 12 strains representing distinct populations (e.g., geographic, temporal, host origin) of E. amylovora was used to describe the pan-genome of this major pathogen. The pan-genome contains 5751 coding sequences and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 67 publications
6
96
2
1
Order By: Relevance
“…On diagnosis, this result shows that only the primers as pEA71, EaIsc are reliable. In addition, other strain of fire blight reported absence of plasmid pEA29 [24], [25].…”
Section: Discussionmentioning
confidence: 99%
“…On diagnosis, this result shows that only the primers as pEA71, EaIsc are reliable. In addition, other strain of fire blight reported absence of plasmid pEA29 [24], [25].…”
Section: Discussionmentioning
confidence: 99%
“…It displayed 98.2% nucleotide sequence identity to the corresponding region in plasmid pEA3. Plasmid pEA3 has a size of 29,585 bp and was originally identified in the plant pathogen Erwinia amylovora CFBP 2585 (GenBank accession number HF560646.1), which causes fire blight, a devastating disease that threatens a wide range of plants, including apple, pear, cotoneaster, and hawthorn shrubs and trees (17,18). Region B also harbored the genes of a type IV secretion system (T4SS) gene cluster (Fig.…”
mentioning
confidence: 99%
“…From the two different primer pairs tested, the primers Peant1/Peant2 and AJ75/AJ76 were much more sensitive and allowed us to detect even small amounts of DNA in the samples where it was not detected using the primers Ea71/72. This is related to the fact that these first two primer pairs are complementary to plasmid pEA29, which occurs in one to five copies per bacterial cell (Mann et al 2013;Smits et al 2010), while primers Ea71/72 are complementary to chromosomal DNA.…”
Section: Resultsmentioning
confidence: 99%
“…E. amylovora is generally considered to be a homogeneous species in terms of phenotypic and genetic features (reviewed by Puławska and Sobiczewski 2012). Recent genomic analysis confirmed that the chromosome of E. amylovora is highly conserved and displays over 99 % amino acid sequence identity among all strains tested (Mann et al 2013). On the other hand, recent application of multi-locus variable number of tandem repeats (MLVA) and clustered regularly interspaced short palindromic repeats (CRISPR) revealed some diversity within E. amylovora (Bühlmann et al 2014;Rezzonico et al 2011).…”
Section: Introductionmentioning
confidence: 99%